Zasoby przedsiębiorstwa a trwałość przewagi konkurencyjnej - Malewska, Kamila (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Sustainable competitive advantage allows the enterprise to keep and develop competitive position in the market for long period of time. Traditional approaches to strategic management tried to identify main sources of competitive advantage in material (tangible) resources such as: capital, equipment, buildings or raw materials. Today both theoreticians and managers pay attention rather to intangible resources and perceive them as a initial source of competitive advantage. The main goal of the article is an analysis of the relation between resources of the enterprise and its competitive advantage in the market. The author also presents essential features of resources that guarantee sustainable competitive advantage. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 212-218